Pengaruh Penambahan Limbah Beton pada Tanah terhadap Unconfined Compression Test - Firman A Due Rego; Meeti; Olan Jujun Sanggaria (Paulus Civil Engineering Journal, 2026)
One method of improving the quality of soil is stability, which can be accomplished by mechanical compaction.  Adding additives is another way to accomplish it.  The addition of concrete waste to the soil is one issue.  Concrete trash is frequently just buried or abandoned, which over time may have a detrimental effect on the environment.  Concrete waste was added to the soil as a soil-binding agent in order to stabilize the soil in this investigation.  Timbuseng Village, Pattalasang District, Gowa Regency, South Sulawesi, had a water content of 28.11% according to soil test data. The Unconfined Compression Test results for the addition of concrete waste used to stabilize clay soil with concrete waste, a soil located in Pangkabinanga, Pallangga District, Gowa Regency, South Sulawesi, show that the unconfined compressive strength test results and the concrete waste vs. qu (kg/cm2) graph for sample 1 (0% qu) are 0.088, 8% (0.102), 16% (0.132), and 24% (0.168). This test shows that each soil sample with a mixture of concrete waste experienced an increase in each variation, resulting in an increase in soil compressive strength, resulting in stronger soil.